O fechamento das escolas do campo em Sergipe : territórios em disputa (2007-2015) - Correia, Elis Santos (2018)
This research approached the closures of rural schools in Sergipe state from 2007 to 2015 and aimed to analyse the historical and social aspects that conducted this process. Our hypothesis is that there is an unequal dispute of development models that caused profound contradictions between the policies for rural development as a territory restricted to economic production and the Social Movements struggle for the construction of a new territory for life production in which education play a strategic role. In order to attain our objective, we sought to appropriate the historical and dialectical materialism method in order to elicit - in its own concreteness of this process - an analysis based on its totality in articulation with the singularity of the country development model with its contradictions, and the specificity encompassed in the closure of rural schools in Sergipe during period ranging. Our bibliographic study was accompanied by documentary research, statistical data from School Census (INEP) and interviews conducted by former municipal managers and leaders of peasant Social Movements in the state. Our results demonstrate evident withdrawal of the State’s role in relation to its offer with the closure of 404 rural schools, of which 296 were extinct and 108 were considered paralysed over the years in question. The closures were more evident in Sergipe’s High Sertão and Center South regions and the justification presented were: empty classrooms, lack of adequate structure at schools, pursuit for improvements in quality of education tied to the end of multigrades and a better financial management for municipal teachers’ payment. However, the peasant social movements’ analysis considers the closures as withdrawal of rights and as a way to empty the countryside. Our historical analysis enabled us to conjecture about this reality and to understand that economic policy on rural area are related to education policies and financing in it. In turn, they are guided by the overlapping of economic rationality over social demands of peasant population. Such comprehension enables us to assess that rural schools are territories in dispute and their closure is due to a policy that promotes the country as a territory restricted to economic production, opposed to the historical struggles for the construction of a counter-hegemonic peasant territory, where Rural Education is born and defended.